Plein air techniques for artists : principles and methods for painting in natural light - Erickson, Aimee, 1967- (For artists series, 2023)
"From award-winning artist Aimee Erickson, Plein Air Techniques for Artists presents the step-by-step process for plein air for landscape, still life, and the figure, along with exercises to strengthen skills"--